MENINGKATKAN KEDISIPLINAN ANAK MELALUI PENGGUNAAN REINFORCEMENT SECARA VARIATIF PADA ANAK KELOMPOK B1 TAMAN KANAK-KANAK NEGERI PEMBINA - Erni Erawati (Universitas Bengkulu, 2018)
Problem of Clasroom Action Research Issues (CAR) is the “ How to Kondergarten State Coach Kepahiang”. The purpose of the Clasroom Action Research (CAR) is that with the use of reinforcement is varied. Subject of study of 20 childern of 9 boys and 11 girls. Action taken in this study consisted of 2 cycle. In cycle I generally acquired 62,25% of children who have increasiddiscipline. In cycle II is generally acquired 89,61% of children who have increased discipline. Cycle II declared a success because the percentage of success criteria of 75%. It can be concluded that the use of reinforcement is varied to improve the discipline of children group B1 Kindergarten State Coach Kepahiang. Key word : Discipline, Reinforcement